A correlation between severe haemolytic disease of the fetus and newborn and maternal ABO blood group. Issue 4 (28th June 2014) - Doyle, B.; Quigley, J.; Lambert, M.; Crumlish, J.; Walsh, C.; McParland, P.; Culliton, M.; Murphy, K.; Fitzgerald, J.
SUMMARY Objective To analyse anti‐D quantification levels and frequency of intrauterine transfusion (IUT), per maternal ABO blood group. Background Maternally derived red cell allo‐antibodies can target fetal red cell antigens in utero leading to haemolytic disease and fetal anaemia. When a clinically significant allo‐antibody is formed the priority is ascertaining the risk to the fetus and maternal ABO blood groups are not considered relevant. Materials and methods This was a 10‐year retrospective, observational study carried out on women referred for anti‐D quantification (n = 1106), and women whose fetuses required an IUT to treat fetal anaemia (n = 62) due to anti‐D, in the Republic of Ireland. Results Relative to the overall incidence of RhD allo‐immunisation by blood group, women of blood group A were more likely to require IUT compared with those who were blood group O (P = 0·002). Conclusion It is known that ABO feto‐maternal compatibility can influence the incidence and level of red cell allo‐antibodies in pregnancy; however, it does not account for the significantly high rate of severe haemolytic disease requiring IUT seen in blood group A women.